Produtividade da mamona, irrigada com esgoto doméstico tratado em lagoas de estabilização - Souza, Neyliane Costa de (2006)
The castor tree (Ricinus communis Linn) represents a huge potential to the economy of the semi-arid region located in the Northeast of Brazil, as an alternative crop for biodiesel production. Effluents reuse in agriculture is a water alternative for regions with water shortage, such as Northeast of Brazil. In this research, the castor seed was irrigated by using a microsprinkler system, tested in four different treatments: raw water and soil fertilization (T1); treated wastewater and soil fertilization (T2); treated wastewater without external soil fertilization (T3); and treated wastewater and half of soil fertilization (T4), each one with four repetitions. The experiment was conducted during 7 (seven) months, between February and August of 2005, in an area attached to a Wastewater Treatment System located in Aquiraz, Metropolitan Region of Fortaleza, Ceará, Brazil. The castor seed variety used was BRS 149 Nordestina. The castor seed was seeded in February 24th of 2005, in an area of 25,5m x 59m, divided in four blocks, with space of 3m and 3,5m among them. Each block contained 10 lines with 6 plants. The crop developing was assessed by the parameters: height, stem thickness, number of leaves and number of nodes, in which was not verified any significant difference among the treatments. The productivity components such as number of racemes, number of fruits, raceme size and total productivity were also monitored. The castor seeds oil content was also investigated, but any significative difference among the treatments with soil fertilization (T1, T2 and T4) was verified. The treatment tested with eflluent without soil fertilization (T3) provided very low oil content in the seeds. The castor seeds production in the treatments with effluent was higher than the one with raw water in almost all the parameters analized. Particularly regarding the productivity, the highest production was obtained in the treatments with wastewater and soil fertilization (T2) and wastewater and half of soil fertilization (T4), achieving a productivity of 1.986 kg/ha and 1.412 kg/ha, respectively.